A Nutritional-Toxicological Assessment of Antarctic Krill Oil versus Fish Oil Dietary Supplements - Bengtson Nash, Susan M; Schlabach, Martin; Nichols, Peter D (Nutrients, 2014)
Fish oil dietary supplements and complementary medicines are pitched to play a role of increasing strategic importance in meeting daily requirements of essential nutrients, such as long-chain (≥C20, LC) omega-3 polyunsaturated fatty acids and vitamin D. Recently a new product category, derived from Antarctic krill, has been launched on the omega-3 nutriceutical market. Antarctic krill oil is marketed as demonstrating a greater ease of absorption due to higher phospholipid content, as being sourced through sustainable fisheries and being free of toxins and pollutants; however, limited data is available on the latter component. Persistent Organic Pollutants (POP) encompass a range of toxic, man-made contaminants that accumulate preferentially in marine ecosystems and in the lipid reserves of organisms. Extraction and concentration of fish oils therefore represents an inherent nutritional-toxicological conflict. This study aimed to provide the first quantitative comparison of the nutritional (EPA and DHA) versus the toxicological profiles of Antarctic krill oil products, relative to various fish oil categories available on the Australian market. Krill oil products were found to adhere closely to EPA and DHA manufacturer specifications and overall were ranked as containing intermediate levels of POP contaminants when compared to the other products analysed. Monitoring of the pollutant content of fish and krill oil products will become increasingly important with expanding regulatory specifications for chemical thresholds.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; miljøgifter; plankton; toksikologi

Venom on ice: First insights into Antarctic octopus venoms - Undheim, E.A.B.; Georgieva, D.N.; Thoen, H.H.; Norman, J.A.; Mork, J.; Betzel, C.; Fry, B.G. (Toxicon, 2010)
The venom of Antarctic octopus remains completely unstudied. Here, a preliminary investigation was conducted into the properties of posterior salivary gland (PSG) extracts from four Antarctica eledonine (Incirrata; Octopodidae) species (Adelieledone polymorpha, Megaleledone setebos, Pareledone aequipapillae, and Pareledone turqueti) collected from the coast off George V’s Land, Antarctica. Specimens were assayed for alkaline phosphatase (ALP), acetylcholinesterase (AChE), proteolytic, phospholipase A2 (PLA2), and haemolytic activities. For comparison, stomach tissue from Cirroctopus sp. (Cirrata; Cirroctopodidae) was also assayed for ALP, AChE, proteolytic and haemolytic activities. Dietary and morphological data were collected from the literature to explore the ecological importance of venom, taking an adaptive evolutionary approach. Of the incirrate species, three showed activities in all assays, while P. turqueti did not exhibit any haemolytic activity. There was evidence for cold-adaptation of ALP in all incirrates, while proteolytic activity in all except P. turqueti. Cirroctopus sp. stomach tissue extract showed ALP, AChE and some proteolytic activity. It was concluded that the AChE activity seen in the PSG extracts was possibly due to a release of household proteins, and not one of the secreted salivary toxins. Although venom undoubtedly plays an important part in prey capture and processing by Antarctica eledonines, no obvious adaptations to differences in diet or morphology were apparent from the enzymatic and haemolytic assays. However, several morphological features including enlarged PSG, small buccal mass, and small beak suggest such adaptations are present. Future studies should be conducted on several levels: Venomic, providing more detailed information on the venom compositions as well as the venom components themselves; ecological, for example application of serological or genetic methods in identifying stomach contents; and behavioural, including observations on capture of different types of prey.
Keywords: Sørishavet; biokjemi; bløtdyr; marin biologi; toksikologi

Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

Determination of Q1, an unknown organochlorine contaminant, in human milk, Antarctic air, and further environmental samples - Vetter, Walter; Alder, Lutz; Kallenborn, Roland; Schlabach, Martin (Environmental Pollution, 2000)
Q1, an organochlorine component with the molecular formula C(9)H(3)Cl(7)N(2) and of unknown origin was recently identified in seal blubber samples from the Namibian coast (southwest of Africa) and the Antarctic. In these samples, Q1 was more abundant than PCBs and on the level of DDT residues. Furthermore, Q1 was more abundant in seals from the Antarctic than the Arctic. To prove this assumption, gas chromatography-electron-capture negative ion mass spectrometry (GC/ECNI-MS), which is sensitive and selective for Q1, allowed for screening of traces of Q1 even in samples with particularly high levels of other organochlorine contaminants. Q1 was isolated by high-performance liquid chromatography (HPLC) from a skua liver sample. A 1:1 mixture with trans-nonachlor in electron-capture detectors (ECDs) was used to determine the relative response factor with ECNI-MS. The ECNI-MS response of Q1 turned out to be 4.5 times higher than that of trans-nonachlor in an ECD. With GC/ECNI-MS in the selected ion-monitoring mode, four Antarctic and four Arctic air samples were investigated for the presence of Q1. In the Antarctic air samples, Q1 levels ranged from 0.7 to 0.9 fg/m(3). In Arctic air samples, however, Q1 was below the detection limit (<0.06 fg/m(3) or 60 ag/m(3)). We also report on high Q1 levels in selected human milk samples (12-230 microg/kg lipid) and, therefore, suggested that the unknown Q1 is an environmental compound whose origin and distribution should be investigated in detail. Our data confirm that Q1 is a bioaccumulative natural organochlorine product. Detection of a highly chlorinated natural organochlorine compound in air and human milk is novel.
Keywords: Antarktis; forurensning; kromatografi; miljøgifter; miljøovervåking; toksikologi